A colorimetric detection strategy and micromotor-assisted photo-Fenton like degradation for hydroquinone based on the peroxidase-like activity of Co3O4–CeO2 nanocages. Issue 23 (31st October 2022) - Hu, Kaiyuan; Li, Jia; Han, Yang; Ng, Dickon H. L.; Xing, Ningning; Lyu, Yangsai
Abstract : Co3 O4 –CeO2 micromotors were fabricated and the colorimetric detection and micromotor-assisted photodegradation capability were studied. Abstract : Micromotors have great potential in environmental monitoring and treatment. Herein, ZIF-67 derived Co3 O4 –CeO2 micromotors with a porous nanocage structure were synthesized by the ingenious combination of template scarification and calcination methods. Co3 O4 inherited the typical porous structure of the ZIF-67 precursor and its skeleton offered a substrate for uniform in situ growth of CeO2 nanoparticles. The ZIF-67 derived Co3 O4 –CeO2 revealed a unique nanocage structure with a broken corner, resulting in the autonomous movement in the presence of H2 O2 . Based on the combination of peroxide-like activity, self-propelled motion and photo-Fenton like performance, a strategy to selectively and sensitively detect and quickly remove hydroquinone (HQ) from water was established. Taken together, this novel Co3 O4 –CeO2 nanocage-based micromotor could be effectively harnessed for water treatment.